TRANSFORMASI PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR MELALUI IMPLEMENTASI MEDIA DIGITAL ESSEMBLR EDU - Aulia Fajar Khasanah; Uci Ulfa Nur’afifah; Arwanda Ahmad Atti Zani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to qualitatively analyze the transformation of learning in primary schools through the implementation of Digital Media Essemblr Edu. The background of this research is based on a paradigm shift in education in the digital era that demands innovation in the teaching and learning process. With a case study approach, this study explores how the use of Essemblr Edu affects teachers ' pedagogical practices, student engagement, and the learning atmosphere in the primary school environment. Data was collected through classroom observation, in-depth interviews with teachers and students, and analysis of curriculum documents and lesson plans. The results showed that the implementation of Essemblr Edu triggered significant transformations that include: increased motivation and active participation of students, personalization of learning experiences through interactive features, and adaptation of teachers ' teaching strategies towards a more facilitative approach. Nevertheless, challenges related to infrastructure and technological adaptation capacity of teachers were also identified. The implications of this study affirm Essemblr Edu's potential as a catalyst for positive change in learning in primary schools, while stressing the importance of comprehensive support for the sustainability of digital innovation.